Assessment of children suicide attempts frequency in the peripandemic period - Wiktor, Łukasz; Damps, Maria (Frontiers in Psychology, 2024)
Objectives: Our study aimed to evaluate patients after suicide attempts treated at the Department of Trauma Surgery for Children in the peripandemic period, assessment of potential risk factors, and the school's participation as the unit responsible for the prevention of suicidal behavior. Material and methods: Retrospective review of the medical database at equal time intervals of 24 months to identify patients treated before and after the COVID-19 was done. Thorough analysis including injury mechanism, medical procedures, history of previous mental disorders or suicidal behavior was performed. Furthermore, results were compared with the Polish police suicide statistics. Results: Based on our retrospective review we found 4 patients treated in our department before the pandemic and 10 patients treated after COVID-19 outbreak. The group before SARS-Cov-2 era consisted of three girls and one boy with a mean age of 14.97 (12.7-17.6). The group treated in the pandemic crisis consisted of 8 boys and 2 girls, the mean age was 15.49 (10.8-17.2). In the pre-COVID-19 group, 2 out of 4 patients had received psychiatric treatment before, but none had attempted suicide before. In the COVID-19 group, 6 out of 10 patients had previously received psychiatric treatment, moreover 3 of them attempted suicide before. Based on our analysis, the number of individuals who displayed suicidal attempts has raised. Between 2018 and 2021 the largest number of suicides concerned the 13-18 y.o. group, both for the Silesian Voivodeship (H=9.374; p=0.0092) and for the whole country (H= 10.203; p=0.0061). Conclusions: 1. Results of our study indicate that the pandemic may have caused a wide range of negative mental health consequences for young individuals; 2. Suicide attempts in children are often related with high energy trauma; 3. Teachers and school psychologists, as well as medical health providers, should be aware of rising suicide rates among adolescents.